Diagnostic evaluation, surgical technique, and perioperative management after esophagectomy: consensus statement of the German Advanced Surgical Treatment Study Group - Palmes, Daniel Michael; Brüwer, Matthias; Bader, Franz G.; Betzler, Michael; Becker, Heinz; Bruch, Hans-Peter; Büchler, Markus W.; Buhr, Heinz; Ghadimi, Beta Michael; Hopt, Ulrich T.; Konopke, Ralf; Ott, Katja; et al. (Langenbeck's archives of surgery, 2011)
PURPOSE: Correct diagnosis, surgical treatment, and perioperative management of patients with esophageal carcinoma remain crucial for prognosis within multimodal treatment procedures. This study aims to achieve a consensus regarding current management strategies in esophageal cancer by questioning a panel of experts from the German Advanced Surgical Treatment Study (GAST) group, comprised of 9 centers specialized in esophageal surgery, with a combined total of >220 esophagectomies per year. - MATERIALS AND METHODS: The Delphi method, a systematic and interactive, evidence-based approach, was used to obtain consensus statements from the GAST group regarding ambiguities and disparities in diagnosis, patient selection, surgical technique, and perioperative management of patients with esophageal carcinoma. After four rounds of surveys, agreement was measured by Likert scales and defined as full (100% agreement), near (≥66.6% agreement), or no consensus (<66.6% agreement). - RESULTS: Full or near consensus was obtained for essential aspects of esophageal cancer staging, proper surgical technique, perioperative management and indication for primary surgery, and neoadjuvant treatment or palliative treatment. No consensus was achieved regarding acceptability of minimally invasive technique and postoperative nutrition after esophagectomy. - CONCLUSION: The GAST consensus statement represents a position paper for treatment of patients with esophageal carcinoma which both contributes to the development of clinical treatment guidelines and outlines topics in need of further clinical studies.
Gesehen am 07.09.2022